Bifunctionalized mesoporous molecular sieve for perchlorate removal - Kim, T.H.; Jang, Min; Park, J.K. (Elsevier, 2008)
Quaternary ammonium functionalized mesoporous media were synthesized for the effective removal of perchlorate. As a support host, mesoporous molecular sieve, SBA-15, was mono- or bifunctionalized with quaternary ammonium ions, N-((trimethoxysilyl)propyl)-N,N,N-trimethylammonium chloride (TSPMC) and N-((trimethoxysilyl)propyl)-N,N,N-tributylammonium chloride (TSPBC), by an incipient wetness impregnation method. Pore structures of the media were characterized by using nitrogen adsorption-desorption isotherms and an X-ray diffraction (XRD) analysis. The perchlorate adsorption speeds and capacities for the mono- or bifunctionalized SBA-15 were also examined, and compared with a conventional anion exchange resin (IRA-900). All the functionalized SBA-15 showed fast adsorption equilibriums within 10 min, while IRA-900 had a quite slow removal speed and did not reach an equilibrium for 5 h, as shown in other studies on a perchlorate removal with organic polymer anion exchange resins. The ammonium bifunctionalized mesoporous medium, 2 mmol of TSPMC and 2 mmol of TSPBC grafted into 1 g of SBA-15 (designated as MB22), showed a 1.14-1.39 (or 1.31-1.88) times higher adsorption capacity (or distribution coefficient) than those of monofunctionalized SBA-15. Compared to IRA-900, MB22 had about a 1400 times faster initial sorption rate. By considering the molecular size-selectivity, biodegradability, and thermal/chemical stability, quaternary ammonium bifunctionalized mesoporous molecular sieves are thought to have lots of merits for a perchlorate-containing water treatment. Â© 2007.